1979
DOI: 10.1113/jphysiol.1979.sp012624
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline as a possible mediator of the actions of angiotensin on fluid transport by rat rejunum in vivo

Abstract: SUMMARY1. Net fluid absorption and transmural potential difference were measured in the rat jejunum in vivo.2. Increased rates of net fluid transport were observed following infusions of angiotensin or noradrenaline. There was a small, but significant, fall in transmural p.d. associated with noradrenaline but not with angiotensin infusions.3. The a-adrenergic antagonists phentolamine and dihydroergotamine abolished both the angiotensin and the noradrenaline stimulations of transport and the noradrenaline-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

1981
1981
1993
1993

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…While substantial evidence is available indicating noradrenergic mediation ofAII-induced ion transport in vivo (Levens et al, 1979;1981) none of the a-or Padrenoceptor antagonists tested in the present study affected All responses in either the jejunum or colon. Yohimbine and phentolamine did, however, block NA-induced reductions in SCC in preparations of jejunum in agreement with an x2-adrenoceptor mechanism of action described by Chang et al (1982).…”
Section: Discussioncontrasting
confidence: 64%
“…While substantial evidence is available indicating noradrenergic mediation ofAII-induced ion transport in vivo (Levens et al, 1979;1981) none of the a-or Padrenoceptor antagonists tested in the present study affected All responses in either the jejunum or colon. Yohimbine and phentolamine did, however, block NA-induced reductions in SCC in preparations of jejunum in agreement with an x2-adrenoceptor mechanism of action described by Chang et al (1982).…”
Section: Discussioncontrasting
confidence: 64%
“…It is well-known that after denervation effector organs become supersensitive to the effects of endogenous neurotransmitter (24). Because exogenous norepinephrine exhibits a dose-dependent dual action on jejunal water transport (9), it is possible in our sympathectomy experiments that denervation supersensitivity could have altered responses ofthe jejunum to endogenously released norepinephrine. However, angiotensin II failed to stimulate jejunal transport at any dose in sympathectomized rats or animals acutely treated with guanethidine.…”
Section: Discussionmentioning
confidence: 86%
“…7). Phentolamine (36 ,g/kg per min) abolishes the stimulation of jejunal water absorption and the associated increase in systemic blood pressure produced by infusion of 7 nmol/ kg per min norepinephrine (9). Similarly, in the present study, pretreatment of the animals with prazosin (200 ,ug) attenuated the increase in blood pressure in response to 7 nmol/kg per min norepinephrine (88±9.0 -151+4.0 to 71+4.9-91+4.0 mm Hg).…”
Section: Resultsmentioning
confidence: 99%
“…Although this effect was blocked by ouabain at 2.5 ng/ml, this level ofouabain Biochemistry: Brock et aL is probably too low to inhibit the Na+/K' pump in rat.tissues (35). Angiotensin peptides are potent stimulators of intestinal Na and water absorption; however, this effect ofAII was shown to be due to the release of norepinephrine from nerve endings in the jejunum (36)..The Na+/K+-ATPase activity ofmicrosomal membranes prepared from certain tissues, but not others, was increased when assayed in the presence of AII (37)(38)(39). Alr though membranes from vascular smooth muscle were not included in previous studies (37-39), we have found that AII had no significant effect on the Na+/K+-ATPase activity in membranes isolated from the smooth muscle cultures (unpublished data).…”
Section: Discussionmentioning
confidence: 99%